A chromosome-scale reference genome assembly for Triplophysa lixianensis - Chunlin He; Xinhui Zhang; Zhengyong Wen; Qiong Shi; Zhaobin Song (Scientific Data)
Abstract In this study, we constructed a chromosome-scale reference genome assembly for Lixian plateau loach, Triplophysa lixianensis, by integration of MGI short-read, PacBio HiFi long-read and Hi-C sequencing technologies. A 668-Mb haplotypic genome assembly was obtained for a female T. lixianensis, and 98.91% of the assembled sequences were anchored into 25 chromosomes. This assembly owned a moderate repeat content (35.63%) and an annotation of 23,774 protein-coding genes, among them 94.15% were predicted with functions. The assembled genome of T. lixianensis shared a good syntenic relationship with previously published data of its relative T. dalaica. Taken together, our genome data presented here provide a valuable genetic resource for in-depth evolutionary and functional studies, as well as molecular breeding and conservation of this valuable fish species to elevate its ecological and economical values.